SANDRA CORREIA FAVERO AND SAMBAQUI (Revista Apotheke, 2021)
This article is the result of an interview and visit at the atelier of professor-researcher-artist Sandra Favero in the neighborhood of Sambaqui, north of the island of Florianópolis (SC) in October 2019. It is sought from the geographical location of the artist to create relations between its production and the way of life of prehistoric men who inhabited the place.